The Effect of Using Dartboard Media on Critical Thinking Skills and Student Learning Outcomes in the Digestive System Topic - Nailasari; Mushawwir Taiyeb; Hartono; Firdaus Daud; Alimuddin Ali (Postgraduate, University of Mataram, 2026)
The development of critical thinking skills and improved learning outcomes are central goals of effective biology instruction. However, conventional learning media often fail to sufficiently stimulate higher-order thinking processes. This study examined the effect of dartboard-based learning media on students’ critical thinking skills and learning outcomes in the topic of the digestive system. A quantitative quasi-experimental design with a pretest–posttest control group structure was employed, involving two grade XI classes at SMA Negeri 8 Gowa assigned as experimental and control groups. Data were collected through validated critical thinking and achievement tests and analyzed using inferential statistics. The results indicated that students taught using dartboard learning media demonstrated significantly higher critical thinking skills and learning outcomes compared to those receiving conventional instruction (p < 0.05). These findings suggest that dartboard-based media effectively promotes active engagement, facilitates higher-order cognitive processes, and enhances academic performance in biology learning contexts.